1994
DOI: 10.1002/ar.1092380203
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure as a basis for dating of rat endometrium

Abstract: Studies on the endometrial cycle depend upon the precise dating of the cycle stage. In the present paper the generally applied method of vaginal smear was carefully verified through the measurement of the hormones relevant to the endometrial cycle. From rats predated through vaginal smear cytology, the hormone levels of estradiol-17-beta (E2) and progesterone (P), luteinizing hormone (LH), and follicle stimulating hormone (FSH) were measured. The values obtained were then compared to the standardized values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
41
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 22 publications
11
41
0
1
Order By: Relevance
“…The present study shows that extra lipid accumulation occurs within the uterine epithelium suggesting that hypothyroidism may influence generally cellular lipid metabolism. The fact that the observed changes in epithelial structure in this study were similar to those found during dioestrus stage of the oestrus cycle in rats by Spornitz et al (36) further suggest that hypothyroidism affects ovarian steroid hormone metabolism. Therefore, alteration in steroid hormone levels during hypothyroidism is especially likely since the dioestrus stage in rats is characterised by low steroid hormone levels, and the hypothyroid rats in this study had a preponderance of dioestrus vaginal smears (12).…”
Section: Discussionsupporting
confidence: 90%
“…The present study shows that extra lipid accumulation occurs within the uterine epithelium suggesting that hypothyroidism may influence generally cellular lipid metabolism. The fact that the observed changes in epithelial structure in this study were similar to those found during dioestrus stage of the oestrus cycle in rats by Spornitz et al (36) further suggest that hypothyroidism affects ovarian steroid hormone metabolism. Therefore, alteration in steroid hormone levels during hypothyroidism is especially likely since the dioestrus stage in rats is characterised by low steroid hormone levels, and the hypothyroid rats in this study had a preponderance of dioestrus vaginal smears (12).…”
Section: Discussionsupporting
confidence: 90%
“…For this purpose endometrial tissue, predated by vaginal smear cytology, was verified by hormone assessment and then investigated by scanning electron microscopy. This study complements the work done by Spornitz et al (1994), who examined intracellular changes in epithelial cells under the same conditions.…”
supporting
confidence: 73%
“…While oestrogen affects the endometrium during the proliferative phase, progesterone induces several morphological and functional changes in the endometrium during the secretory phase of the cycle. The secretory changes in the endometrial epithelial and stromal compartments are well documented (Noyes et al, 1950;Li et al, 1991;Spornitz et al, 1994). Morphological features in the control endometrium similar to those reported by above investigators were also observed in the present study.…”
Section: Resultssupporting
confidence: 91%
“…Several studies indicated an increased secretory function, and a change in endometrial glandular epithelial structure in humans, rats and sheep (Smith et aL, 1990; Li et al, 1991; Blankenship and Given, 1992; Spornitz et al, 1994). Along with this secretory activity, epithelial cells increase their number of nuclei, then differentiate into a special type of cell, the so-called Arias-Stella cells.…”
Section: Resultsmentioning
confidence: 99%